TissueCypher Barrett’s esophagus assay impacts clinical decisions in the management of patients with Barrett’s esophagus - Diehl, David L.; Khara, Harshit S.; Akhtar, Nasir; Critchley-Thorne, Rebecca J. (Endoscopy International Open, 2021)
Background and study aims The TissueCypher Barrett’s Esophagus Assay is a novel tissue biomarker test, and has been validated to predict progression to high-grade dysplasia (HGD) and esophageal adenocarcinoma (EAC) in patients with Barrett’s esophagus (BE). The aim of this study was to evaluate the impact of TissueCypher on clinical decision-making in the management of BE.Patients and methods TissueCypher was ordered for 60 patients with non-dysplastic (ND, n = 18) BE, indefinite for dysplasia (IND, n = 25), and low-grade dysplasia (LGD, n = 17). TissueCypher reports a risk class (low, intermediate or high) for progression to HGD or EAC within 5 years. The impact of the test results on BE management decisions was assessed.Results Fifty-two of 60 patients were male, mean age 65.2 ± 11.8, and 43 of 60 had long segment BE. TissueCypher results impacted 55.0 % of management decisions. In 21.7 % of patients, the test upstaged the management approach, resulting in endoscopic eradication therapy (EET) or shorter surveillance interval. The test downstaged the management approach in 33.4 % of patients, leading to surveillance rather than EET. In the subset of patients whose management plan was changed, upstaging was associated with a high-risk TissueCypher result, and downstaging was associated with a low-risk result (P < 0.0001). Conclusions TissueCypher was used as an adjunct to support a surveillance-only approach in 33.4 % of patients. Upstaging occurred in 21.7 % of patients, leading to therapeutic intervention or increased surveillance. These results indicate that the TissueCypher test may enable physicians to target EET for TissueCypher high-risk BE patients, while reducing unnecessary procedures in TissueCypher low-risk patients.